Kajian Implementasi Program Pembangunan Ruang Terbuka Hijau di Kota Tangerang Selatan Tahun 2012 - 2016 - Kurniawan, Muhammad Budi; Astuti, Puji; Adnan, Muhammad (Journal of Politic and Government Studies, 2017)
Arrangement of a city is an important part in order to regional development which is one of the duties and obligations of the government, both central and local government. In the arrangement of urban areas, of course, the government must also pay attention to aspects of the environment in order to realize the development of environmentally based urban areas. Policy of arrangement and maintenance of Urban Open Space (UOS), is one of the policies of the development of an environment-based area. This study is a policy study that examines how the implementation of development, supervision, and maintenance, conducted by the South Tangerang City Government as one of the realization of â€œRencana Tata Ruang Wilayahâ€ (RTRW) of South Tangerang City in 2011-2031, as embodied in the Regional Regulation of South Tangerang City No. 15 of 2011. This research uses descriptive qualitative method with data collection techniques through in-depth interviews and documents. The main focus of this research is the context of policy implementation related to the strength of existing legal products, the interests of the actors involved, the characteristics of implementing agencies, and the compliance and responsiveness of the implementers in the field.Keywords: Development, Supervision, Urban Open Space, Environment, Policy